Age-Dependent Impairment of Neurovascular and Neurometabolic Coupling in the Hippocampus - Lourenço, Cátia F.; Ledo, Ana; Caetano, Miguel; Barbosa, Rui M.; Laranjinha, João (Frontiers in Physiology, 2018)
Neurovascular and neurometabolic coupling are critical and complex processes underlying brain function. Perturbations in the regulation of these processes are, likely, early dysfunctional alterations in pathological brain aging and age-related neurodegeneration. Evidences support the role of nitric oxide (•NO) as a key messenger both in neurovascular coupling, by signaling from neurons to blood vessels, and in neurometabolic coupling, by modulating O2 utilization by mitochondria. In the present study, we investigated the functionality of neurovascular and neurometabolic coupling in connection to •NO signaling and in association to cognitive performance during aging. For this, we performed in vivo simultaneous measurements of •NO, O2 and cerebral blood flow (CBF) in the hippocampus of F344 rats along chronological age in response to glutamatergic activation and in correlation with cognitive performance. Firstly, it is evidenced the temporal sequence of events upon glutamate stimulation of hippocampal dentate gyrus, encompassing the local and transitory increase of •NO followed by transitory local changes of CBF and pO2. Specifically, the transient increase of •NO is followed by an increase of CBF and biphasic changes of the local pO2. We observed that, although the glutamate-induced •NO dynamics were not significantly affected by aging, the correspondent hemodynamic was progressively diminished accompanying a decline in learning and memory. Noteworthy, in spite of a compromised blood supply, in aged rats we observed an increased ΔpO2 associated to the hemodynamic response, suggestive of a decrease in the global metabolic rate of O2. Furthermore, the impairment in the neurovascular coupling observed along aging in F344 rats was mimicked in young rats by promoting an unbalance in redox status toward oxidation via intracellular generation of superoxide radical. This observation strengthens the idea that oxidative stress may have a critical role in the neurovascular uncoupling underlying brain aging and dysfunction. Overall, data supports an impairment of neurovascular response in connection with cognition decline due to oxidative environment-dependent compromised •NO signaling from neurons to vessels during aging.